O ruído no ambiente escolar do ensino fundamental I como barreira no processo de inclusão de crianças com transtorno do espectro autista - (:unkn) unknown (Universidade Brasil, 2021)
The regular school environment is still hostile for children and adolescents with autism spectrum disorder, since the process of school inclusion depends not only on the pedagogical adaptation, but also on the environment adaptation, combating external factors which act as an educational barrier, mainly with the student with auditory hypersensitivity. In view of the difficulties in sensory processing and cases of auditory hypersensitivity in the autistic person, adapting the school structure becomes essential for the student inclusion, making it necessary to draw attention to the mandatory nature of this structure and the responsibility of the educational institution to prepare the school environment to receive the student with special educational needs. In view of the structural barriers of schools, the use of adaptive resources, such as noise dampeners, becomes the most effective and quickest alternative to the process of school inclusion, being the responsibility of the institutions to supply them, as demonstrated in this article. Therefore, the present study correlated findings from descriptive research involving concepts about autism, hearing sensitivity, noise pollution and inclusive education, to the official data from the Brazilian legislation on the process of inclusion of children with autism spectrum disorder in regular education, defending the hypothesis of the need to adapt the school environment to minimize the negative impacts of noise and assist the process of inclusion of the autistic child.
Keywords: Abafadores de ruídos; Barreira de aprendizagem; Inclusão escolar; Recurso adaptativo; Legislação Ambiental